If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(p + 8q + -13) = 0 Reorder the terms: 5(-13 + p + 8q) = 0 (-13 * 5 + p * 5 + 8q * 5) = 0 (-65 + 5p + 40q) = 0 Solving -65 + 5p + 40q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '65' to each side of the equation. -65 + 5p + 65 + 40q = 0 + 65 Reorder the terms: -65 + 65 + 5p + 40q = 0 + 65 Combine like terms: -65 + 65 = 0 0 + 5p + 40q = 0 + 65 5p + 40q = 0 + 65 Combine like terms: 0 + 65 = 65 5p + 40q = 65 Add '-40q' to each side of the equation. 5p + 40q + -40q = 65 + -40q Combine like terms: 40q + -40q = 0 5p + 0 = 65 + -40q 5p = 65 + -40q Divide each side by '5'. p = 13 + -8q Simplifying p = 13 + -8q
| -25+y=2 | | 3-4x=-5 | | 10.8=2.7r | | 1.3+0.1x=0.7x-2.3 | | x^2-2ax+a^2=0 | | (2x^2-1)(6x+4)= | | .33x=-3.11 | | 3x+4=2(x-5) | | 2ln(x)-2=ln(x-3) | | 5w+12=-78 | | 5.4q-1.6-5.7q=-1.3q-1.4 | | 3(6z-1)-5(z+9)=7(z+1) | | (x)(x)+3=19 | | -3x+6=-4 | | 9.6x+18-9.9x-7.8= | | 3x+5(x-2)=14 | | x+1=37+10 | | 5x^2-x+15=0 | | 3y-6=11 | | 8x+24=3x+4 | | 3x-1=29 | | 33334+3456789986= | | 12(5-x)=72 | | 3x-15=-15 | | 6t-18+8t=14t+35-8 | | 4x-6=5x+6 | | y=3-3y | | 7*-1+1= | | 7*-2+4= | | 7*-10+4= | | 5x+50=500 | | 3(x+1)=8 |